STRATEGI PEMASARAN DALAM MENGHADAPI PERSAINGAN BISNIS UMKM KULINER KOTA PALEMBANG - Zahira Indah Kurnia; Devi Permata; Indah Nurjanah; Sahwa Adhelia Gubara; Merlin Sagita (Journal of Economics and Development, 2026)
Digital transformation through the growth of e-commerce has become one of the key factors in helping small businesses in Indonesia grow, especially in expanding market access and improving transaction efficiency. On the other hand, the lack of access to appropriate funding sources remains the main obstacle in supporting the development and sustainability of small businesses. Bank syariah offer an alternative that is based on fairness, transparency, and partnership, but how effective it is depends a lot on how business people feel about the products and processes they offer. This study aims to thoroughly examine the role of e-commerce and the perception of business owners regarding the effectiveness of Islamic bank financing in increasing income and the sustainability of small businesses. This study uses a qualitative approach with a descriptive method, collecting data through in-depth interviews, observations, and documentation of small business owners who use e-commerce and access Islamic financing. Research results show that using e-commerce has made a big difference in increasing sales volume, expanding market reach, and improving business operations efficiency. Besides that, positive perceptions of business actors towards Islamic bank financing, especially regarding the ease of procedures, profit-sharing system, and alignment with Sharia principles, influence the level of use of such financing. However, there are still challenges such as low financial literacy in Islamic finance, limited information, and the perception of complexity in financing products, which hinder the optimal use of these services. Overall, the combination of using e-commerce and access to Islamic bank financing, supported by increased understanding and business literacy, has been proven to boost income and strengthen the sustainability of small businesses in the long term.